Comparing the effectiveness and safety of dual antiplatelet with ticagrelor or clopidogrel in elderly Asian patients with acute myocardial infraction - Yeh, Jong-Shiuan; Chen, Wan-Ting; Tomlinson, Brian; Tam, Weng-Chio; Chien, Li-Nien (Frontiers in Cardiovascular Medicine, 2023)
Background Current guidelines recommend potent P2Y12 inhibitors for patients after acute coronary syndrome. However, the data on the efficacy and safety of potent P2Y12 inhibitors in elderly Asian populations was limited. We aimed to investigate the major adverse cardiovascular events (MACE), bleeding events, and net adverse clinical events (NACE) with ticagrelor and clopidogrel in Taiwanese patients aged 65 and older after acute myocardial infarction (AMI). Methods This retrospective population-based cohort study was conducted using data from the National Health Insurance Research Database. The AMI patients aged ≥65 years who underwent percutaneous coronary intervention (PCI) and survived after 1 month were included. The patients were separated into 2 cohorts depending on the type of dual antiplatelet therapy (DAPT) they received: ticagrelor plus aspirin (T+A) or clopidogrel plus aspirin (C+A). We used inverse probability of treatment weighting to balance the difference between these 2 study groups. The outcome included all-cause mortality, MACE (cardiovascular death, nonfatal ischemic stroke, and nonfatal myocardial infarction), intracerebral hemorrhage, major bleeding, and NACE which is composed of cardiovascular death, ischemic and hemorrhagic events. The follow-up period was up to 12 months. Results From 2013 to 2017, a total of 14,715 patients who met the eligibility criteria were separated into 2 groups: 5,051 for T+A and 9,664 for C+A. Compared to patients with C+A, patients who received T+A had a lower risk of cardiovascular death and all-cause death, with an adjusted HR of 0.57(95% confidence interval [CI], 0.38 to 0.85, p=0.006) and 0.58 (95% CI 0.45 to 0.74, p<0.001), respectively. No differences were found in MACE, intracranial and major bleeding between the 2 groups. In addition, the patients with T+A had a lower risk of NACE with an adjusted HR of 0.86 (95% CI 0.74 to 1.00, p=0.045) Conclusions Among elderly AMI patients receiving DAPT after successful PCI, ticagrelor was a more favorable P2Y12 inhibitor than clopidogrel because of lowering the risk of death and NACE without increasing the risk of severe bleeding. Ticagrelor is an effective and safe P2Y12 inhibitor in Asian elderly survivors after PCI.